KEPERCAYAAN KONSUMEN, KEWAJARAN HARGA, DAN SOCIAL MEDIA MARKETING: FAKTOR UTAMA DALAM KEPUTUSAN PENGGUNAAN JASA PREMIUM CUT DI CHIGANOZ BARBERSHOP DENPASAR - I Gusti Ngurah Jaya Winata; Ni Putu Cempaka Dharmadewi Atmaja; Daniel Manek3 (Jurnal Bakti Saraswati (JBS), 2025)
The phenomenon of the mushrooming of barbershops in Indonesia, especially in Denpasar, shows great potential in the men's haircut service industry. Chiganoz Barbershop, one of the major players in the industry, faces challenges in maintaining competitiveness, especially in premium cut services that show fluctuations in revenue. This study aims to analyze the influence of consumer trust, price fairness, and social media marketing on the decision to use premium services at Chiganoz Barbershop Denpasar. Data was obtained through a survey of 70 respondents who were customers of the barbershop. The results of the study show that consumer trust and social media marketing have a positive and significant influence on the decision to use services, while price fairness does not have a significant influence. These findings indicate the importance of building consumer trust through quality service and the use of effective marketing strategies on social media to increase customer preferences for premium services.